Overcoming the shortcomings of HR plans in Kazi Printing and Accessories and some proposed solutions - Ahmed, Asif (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.